PENGARUH TINGKAT INFLASI DAN PENGANGGURANTERHADAP PERTUMBUHAN EKONOMI - Rina Maulina; Jul Fahmi Salim; Rollis Juliansyah (Universitas Teuku Umar, 2018)
This study aims the relationship between the economic growth, Inflation and unemployment in Indonesia by using the time series data from 2007:q1-2016:q4. The study employ the recently developed using Autoregressive Distributed Lag (ARDL) model. Eviews version 9 were used for model estimation. Model estimation showed the significant and negative effect of inflation on economic growt in long term, which indicated that inflation decreased economic growth in the long term. In the short term GDP lag 1 has positive and significant effect on economic growt, in other word inflation lag 1 and inflation lag 2 have negative and significant effect on economic growth. This issue revealed that authorities should diligently endeavor and plan tu reduce inflation and increasing all of economic sector to increasing GDP in short term and long term. The result of this study can be used by all respect authorities in Indonesia, especially economic and social institution. Keywords: Inflation, Economic Growth, GDP, Bound Test, Unemployment, ARDL Approach